ANALYTICS ON SUGARCRM USING MICROSOFT AZURE - Apurva Satarkar; Chinmay Kale; Rahul Dagade; Ridhima Bhalerao (International Journal of Innovations in Engineering Research and Technology, 2021)
Enterprises use theCRM(Customerrelationship management)tomanagethedataabouttheircustomersandanalyse it throughout the customer life cycle so astoimprove business relationship with the customers. The usefulnessof this data is limited. When you add analytics on top of CRM, it provides better understanding and insight aboutthe behaviour of the customer and maximizethe profit.Our application focuses on SugarCRM database which is an open source software. It connects theSugarCRM users withtheservicesofMicrosoftAzureMachineLearningandprovide output in terms of graphs, predictions andsuggestions